Evaluation of the effectiveness of botulinum toxin injection on reducing phantom pain in patients - Reza Alizadeh; Mehrdad Taheri; Siavash Beiranvand; Bahar Fereydoonnia (Interdisciplinary Neurosurgery, 2023)
Objective: Phantom pain is very common in amputations and is associated with severe pain followed by distress and poor quality of life. The aim of this study is to evaluate the effectiveness of botulinum toxin injection in reducing phantom pain in patients referred to Imam Hossein Hospital. Materials and methods: In this double-blinded placebo study, 30 patients with phantom pain referred to Imam Hossein Hospital were included. The participants were divided into two groups of 15 intervention and placebo. In the intervention group, botulinum toxin A was injected to reduce pain in patients and normal saline was injected in placebo group. Patients' pain relief was assessed at 0, 2, 4, 8, and 16 weeks of the treatment. Data were analyzed using SPSS 23 software. Results: Botulinum toxin A injection significantly reduced phantom pain in intervention group at 0, 2, 4, 8, and 16 weeks of the treatment p < 0.05. This reduction was also seen in regard to the cause of amputation, such as war, accidents, and unknown causes. Conclusion: The use of botulinum toxin A seems to be effective in reducing pain in patients with phantom pain. Comparative studies and comparisons of the effect of botulinum toxin with common treatments are recommended.